2022
DOI: 10.1111/jan.15325
|View full text |Cite
|
Sign up to set email alerts
|

Impact of family visit restrictions due to COVID‐19 policy on patient outcomes: A cohort study

Abstract: Aim To investigate the impact of family visit restrictions during the COVID‐19 pandemic on deliriums, falls, pneumonia, pressure ulcers and readmissions among surgical inpatients with gastrointestinal (oncologic) diseases. Design Cohort study. Methods This study was conducted among adult inpatients undergoing gastrointestinal surgery in two academic hospitals. During the COVID‐19 outbreak in 2020, over a 10‐week period, one cohort was subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Despite the perceived excessive workload, nurses reported no reduced quality of care and did not refer to care left incomplete or undone, a frequent problem for COVID_19 patients [39]. In fact, some reported that they developed greater closeness and communication with the patient because of the absence of family members demonstrating high levels of professionalism [40,41]. However, Hargreaves and colleagues (2022) emphasized nurses' concern about not being able to provide the same quality of care as before the pandemic [7].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the perceived excessive workload, nurses reported no reduced quality of care and did not refer to care left incomplete or undone, a frequent problem for COVID_19 patients [39]. In fact, some reported that they developed greater closeness and communication with the patient because of the absence of family members demonstrating high levels of professionalism [40,41]. However, Hargreaves and colleagues (2022) emphasized nurses' concern about not being able to provide the same quality of care as before the pandemic [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of telehealth, and specifically the use of video calls is also growing in hospital wards. Currently, video call interventions are widely implemented in hospital wards and during the COVID-19 pandemic, these video calls appeared to be a valuable communication tool to involve families during hospital admission and to keep families in contact with patients and their healthcare professionals (Bloemberg et al, 2022;Dhahri et al, 2021;Maaskant et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Volunteering across all sectors of health and social care, education and food supply chains was needed on a scale not previously seen. The pandemic was a catalyst for digital transformation, and in nursing we saw that clearly through rapid increases in telehealth (Searby & Burr, 2021; Walthall et al, 2022), changed practices in relation to hospital visiting (Altman et al, 2021; Bloemberg et al, 2022; Lim et al, 2022) and in teaching and learning practices in nurse education (Iradukunda & Canty, 2023; Kimani, 2023; Usher et al, 2023).…”
mentioning
confidence: 99%